Risk Factors for Community-Acquired Extended-Spectrum Beta-Lactamase–Producing Enterobacteriaceae Infections—A Retrospective Study of Symptomatic Urinary Tract Infections. (3rd January 2019) - Goyal, Dheeraj; Dean, Nathan; Neill, Sarah; Jones, Peter; Dascomb, Kristin
Abstract: Background: Community-acquired extended-spectrum beta-lactamase–producing Enterobacteriaceae (ESBL) infections are an evolving public health problem. Identifying predictive risk factors may improve patient management. Methods: We identified 251 adult inpatients admitted to a 22-hospital system with an ESBL urinary tract infection (UTI) between 2001 and 2016. Cases were matched 1:1 with controls who had a UTI at admission with non-ESBL Enterobacteriaceae . Cases with a history of ESBL infections or hospitalization within 3 months of index admission were excluded. Univariate and multiple logistic regression were used to identify risk factors associated with ESBL UTIs. Results: In univariate analysis, history of repeated UTIs, neurogenic bladder, urinary catheter presence at admission, and exposure to outpatient third-generation cephalosporins or fluoroquinolones within 3 months were associated with higher risk of ESBL UTIs. When controlling for severity of illness and comorbid conditions, history of repeated UTIs (adjusted odds ratio [aOR], 6.40; 95% confidence interval [CI], 3.42–12.66; P < .001), presence of urinary catheter at admission (aOR, 2.36; 95% CI, 1.15–4.98; P < .05), and prior antibiotic exposure (aOR, 7.98; 95% CI, 2.92–28.19; P < .001) remained associated with risk of ESBL infection. Conclusions: Patients in the community with indwelling urinary catheters, history of recurrent UTIs, or recent antimicrobial use are at higher risk for de novo ESBL Enterobacteriaceae UTIs.